PENGARUH PERMAINAN TRADISIONAL GOBAK SODOR DALAM BIMBINGAN KELOMPOK TERHADAP PENINGKATAN INTERAKSI SOSIAL ANAK AUTIS - Fitriyah, Fifi Khoirul (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2019)
The prevalence of autism in both Indonesia and the world is increasing from year to year. This causes the problem of autism to be a serious problem not only in the health sector but also in education. Until now, the cause of autism can not be ascertained even that the solution is not optimal. Through the implementation of guidance and counseling in schools, teachers try to overcome the problems of autistic children, especially the problem of low social interaction abilities. The purpose of this study is to test Gobak Sodor Game in group guidance to improve the social interaction abilities of children with autism. This study uses quantitative with a single subject type AB design. The results of this study indicate an increase in the social interaction ability of autism children after the implementation of Gobak Sodor Game in group guidance. In addition, new findings from this study involve children's participation in building interactions with autistic children. This is really positive for both parties, namely autistic children and also normal children who join in the game.